A short note on modelling the three-phase equilibrium conditions of TBAB semi-clathrates formed in the presence of gas mixtures containing CO2. (February 2018) - Michel, N.; Clarke, M.A.
Highlights: Equilibrium for TBAB semi-clathrates from mixed gases is modelled. Model is based on that of Paricaud. No new parameters were needed, except for systems containing CO. Kihara potential parameters are regressed for CO, in TBAB semi-clathrate. Model predictions are reasonably accurate. Abstract: The model of Paricaud (2011) has previously been shown to be able to accurately correlate the three-phase equilibrium conditions of TBAB semi-clathrates in the presence of pure CO2 . While the model of Paricaud (2011) was derived in a manner that was expected to make it relatively straight forward correlating the three-phase equilibrium conditions of semi-clathrates in the presence of mixed gases this capability has not, at the time of writing, been tested. In the present work, the model of Paricaud (2011), along with the modification of Garcia et al. (2016), is examined for its ability to correlate the three-phase equilibrium conditions of TBAB semi-clathrates formed in the presence of binary mixtures of (CO2 + N2 ), (CO2 + H2 ), (CO2 + CH4 ), and (CO2 + CO) and in the presence of a ternary mixture of (CO2 + H2 +CO). The computations were carried out at temperatures between (281 and 293) K, at pressures between (2.0 and 6.6) MPa and in aqueous TBAB solutions of wTBAB = (0.05, 0.10, and 0.20). The average absolute relative deviation of the correlations ranged from 3.7%, for TBAB semi-clathrates formed in the presence of an equimolar mixture of (CO2 + N2 ), to 7.1%, for TBAB semi-clathrates formed in the presence of a ternary gas mixture of (CO2 + H2 +CO).